Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The following series converges? $\displaystyle \sum_{n=0}^{\infty}\frac{1 \cdot 3 \cdot 5 \cdot \dots \cdot (2n-1)(-1)^n }{2 \cdot 4 \cdot 6 \cdot 8 \cdot \dots \cdot (2n)} $ Already concerned with the criteria of reason and Kummer

share|improve this question
    
What have you tried? What happened when you tried it? Save everyone a lot of work by warning of blind alleys. –  Gerry Myerson Nov 29 '12 at 5:22
    
Can you see that your $n$th term is $(-1)^n\frac{1}{4^n}\binom{2n}{n}$? –  alex.jordan Nov 29 '12 at 5:27
    
Are you sure this starts at n = 0 or should that be n = 1? –  Amzoti Nov 29 '12 at 5:29
    
@Amzoti For $n=0$, the interpretation is that both numerator and denominator are empty products, and equal to $1$. –  alex.jordan Nov 29 '12 at 5:30
    
@Alex: Thanks for the clarification - for some reason that threw me off. –  Amzoti Nov 29 '12 at 5:31

3 Answers 3

up vote 4 down vote accepted

Note that $$\begin{align}\frac{1\cdot3\cdot5\cdots\cdot(2n-1)}{2\cdot4\cdot6\cdot\cdots\cdot(2n)} &=\frac{1\cdot2\cdot3\cdots\cdot(2n)}{(2\cdot4\cdot6\cdot\cdots\cdot(2n))^2}\\ &=\frac{(2n)!}{2^{2n}(1\cdot2\cdot3\cdot\cdots\cdot n)^2}\\ &=\frac{(2n)!}{2^{2n}(n!)^2}\\ \end{align}$$

By Stirling's Approximation for factorials, $$\begin{align}\frac{(2n)!}{2^{2n}(n!)^2} &\leq\frac{e(2n)^{2n+1/2}e^{-2n}}{2^{2n}(\sqrt{2\pi}n^{n+1/2}e^{-n})^2}\\ &=\frac{e(2n)^{2n+1/2}e^{-2n}}{2^{2n}(2\pi)n^{2n+1}e^{-2n}}\\ &=\frac{e(2n)^{1/2}}{(2\pi)n}\\ &=\frac{e(2n)^{1/2}}{(2\pi)n}\\ &=\frac{e}{\pi\sqrt{2n}}\longrightarrow0 \end{align}$$

So you have an alternating series whose terms converge to $0$. Also, $$\frac{1\cdot3\cdot5\cdots\cdot(2n-1)(2n+1)}{2\cdot4\cdot6\cdot\cdots\cdot(2n)(2n+2)}<\frac{1\cdot3\cdot5\cdots\cdot(2n-1)}{2\cdot4\cdot6\cdot\cdots\cdot(2n)}$$ So your terms are decreasing in absolute value. The alternating series test guarantees convergence.

And you can even establish what the series converges to. $$\begin{align} \sum_{n=0}^{\infty}(-1)^n\frac{(2n)!}{2^{2n}(n!)^2} &=\sum_{n=0}^{\infty}(-1)^n\frac{1}{4^n}\binom{2n}{n}x^n\\ &=\sum_{n=0}^{\infty}\binom{-1/2}{n}x^n\\ \end{align}$$ where $x=1$. The change to $\binom{-1/2}{n}$ is easy enough to check, and is nice to know every now and then. This last expression is the powers series for $1/\sqrt{1+x}$. With $x=1$, we are right on the boundary of convergence. But we have already established that the series converges with $x=1$. By a theorem of Abel cited at the very beginning of this paper, we may conclude that the series sums to $1/\sqrt{2}$.

share|improve this answer

Partial Answer:

Let

$$a_n= \frac{1 \cdot 3 \cdot 5 \cdot \dots \cdot (2n-1) }{2 \cdot 4 \cdot 6 \cdot 8 \cdot \dots \cdot (2n)} \,.$$

Then

$$a_{n}=\frac{2n-1}{2n}a_{n-1} \,,$$ thus $a_n$ is decreasing.

Because of this, there are only two possible outcomes:

Case 1: $\lim_n a_n=0$, in which case you can use the Alternating Series Test.

Case 2: $\lim_n a_n \neq 0$, in which case the series is divergent.

So, basically your question reduces to: Is

$$\lim_n a_n =0 \, ? \,.$$

share|improve this answer
    
In your expressions for the limits, why do you just put $n$ instead of $n\to\infty$? What I mean is $\lim_n a_n$ vs. $\lim_{n\to\infty} a_n$ –  Joe Nov 29 '12 at 18:26
    
@Joe, the $_{\to\infty}$ is taken as understood from the context. –  Gerry Myerson Nov 30 '12 at 2:40
    
@Gerry That's what I presumed. Thanks. –  Joe Nov 30 '12 at 2:47

Let $$a_n = \prod_{k=1}^n \frac{2 k - 1}{2 k}.$$ Then $$\arcsin(x) = \sum_{n=0}^{\infty} \frac{a_n}{2n+1}x^{2 n + 1}$$ and in particular the series $\frac{a_n}{2n + 1}$ is summable with sum $\frac{\pi}{2}$. (For an elementary proof see this answer.) Since the series $\frac{1}{2n+1}$ is itself not summable and $a_n$ is a decreasing sequence this implies that $\lim_{n \to \infty} a_n = 0$ and therefore your alternating series is summable.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.